THE PROBLEMS OF ENGINEERING PEDAGOGY TERMS INTERPRETATION IN THE INTERNATIONAL COMMUNICATION - T. Y. Polyakova (Moscow Polytechnic University, 2018)
The paper draws attention to ambiguous interpretation of engineering pedagogy terms in the process of international professional communication. It describes some examples of misunderstanding of the terms and inadequate translation of them into Russian. Compiling a terminology English-Russian and Russian-English concise dictionary "Engineering Pedagogy" will contribute to solving this problem for Russian specialists of engineering education. The dictionary is one of the issues of the series of learners' terminology bilingual and multilingual concise dictionaries published by Moscow Automobile and Road Construction State Technical University (MADI). The idea of compiling a multilingual glossary has been supported by International Society for Engineering Pedagogy (IGIP). The dictionary "IGIP Multilingual Glossary" is being compiled now. Both dictionaries are based on the lexicographical concept worked out for the MADI series of concise dictionaries. The paper also describes the main terminological problems to be solved in the process of compiling the dictionaries.